2009
DOI: 10.1007/s10517-009-0466-6
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Rats with Experimental Chronic Heart Failure and Long-Term Exposure to β-Adrenoblockers

Abstract: Simulation of chronic heart failure in rats led to an increase in heart rate variability and decrease in heart rate. All beta-blockers also promoted the heart rate variability augmentation in ill animals. The most potent effects on heart rate variability were produced by pindolol, atenolol, and propranolol. Bisoprolol and metoprolol affected heart rate and heart rate variability in less extent, and nebivolol normalized a part of heart rate variability parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The decrease in HF values and a concomitant change in LF/HF ratio corresponded to a decrease of parasympathetic tone. Both the results of experimental studies in rats and clinical observations in humans and dogs imply that HRV parameters may change during pharmacotherapy of heart failure, irrespective of its etiology (Tacoy et al 2007, Nolan et al 2008, Sal'nikov 2009, Henze et al 2013, Chom-poosan et al 2014, Dias da Silva et al 2015. Consequently, ST-HRV parameters may soon be applied as prognostic and predictive markers in dogs treated due to CMVD.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in HF values and a concomitant change in LF/HF ratio corresponded to a decrease of parasympathetic tone. Both the results of experimental studies in rats and clinical observations in humans and dogs imply that HRV parameters may change during pharmacotherapy of heart failure, irrespective of its etiology (Tacoy et al 2007, Nolan et al 2008, Sal'nikov 2009, Henze et al 2013, Chom-poosan et al 2014, Dias da Silva et al 2015. Consequently, ST-HRV parameters may soon be applied as prognostic and predictive markers in dogs treated due to CMVD.…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with decompensated heart failure, beta-blockers were associated with better frequency-domain HRV parameters (total power and ULF) [ 65 , 94 ]. An experimental study with a rat model of chronic heart failure also reported similar findings, with atenolol and pindolol increasing both LF and HF power [ 95 ]. This study revealed augmentation of HRV with the use of beta-blockers supporting their use in patients with heart failure [ 95 , 96 ].…”
Section: Resultsmentioning
confidence: 62%
“…An experimental study with a rat model of chronic heart failure also reported similar findings, with atenolol and pindolol increasing both LF and HF power [ 95 ]. This study revealed augmentation of HRV with the use of beta-blockers supporting their use in patients with heart failure [ 95 , 96 ]. Another element of perioperative medical management is amiodarone, which also reduces the risk of post-operative AF.…”
Section: Resultsmentioning
confidence: 62%